HUBUNGAN EDUCATOR PERAWAT DALAM DISCHARGE PLANNING DENGAN TINGKAT KEPATUHAN PASIEN RAWAT INAP RUANGAN 7 WEST UNTUK KONTROL DI MURNI TEGUH MEMORIAL HOSPITAL - Hutabarat, Teressi A.; Mendrofa, Hendry Kiswanto (Indonesian Trust Nursing Journal, 2025)
Discharge planning results in an integrated relationship when the patient receives care in the hospital and the care given after the patient goes home. Discharge planning requires good and directed communication so that the patient can understand and benefit when the patient is at home. This is one of the important factors that makes patients obedient to return to the hospital for control. The purpose of this study was to determine the relationship between nurse educator in discharge planning with the level compliance of inpatients for check-ups at Murni Teguh Memorial Hospital. This study is a quantitative study with a correlational study design using a cross-sectional approach. The study was conducted at Murni Teguh Memorial Hospital. The sample in this study amounted to 30 respondents with purposive sampling technique. Data analysis used the Chi-Square test. The result of this study with the chi-square test showed a relationship between nurse educator in discharge planinng with the level of compliance of inpatients for check-ups as indicated by a p-value <0.05. It is recommended for further researchers to add research variables such as factors related to patient compliance in treatment.